Impactful behavioural therapy (IBT) in obesity care - Sanjay Kalra,; Madhur Verma,; Nitin Kapoor, (Journal of the Pakistan Medical Association, 2025)
Intensive behavioural therapy is said to be the first linetreatment of obesity. The choice of the adjective‘intensive’, however, is open to debate. The term‘impactful behavioural therapy’ seems more appropriatefor the management of persons living with obesity. Thisrefers to a sustained supportive psychosocialintervention, embedded in routine care, designed tomodify existing behaviours, and maintain desired ones, inpersons living with obesity, and their caregivers, so as toachieve optimal, sustainable weight. The characteristicsand contents of such therapy are described in thiscommunication. Keywords: Behavioural therapy, chronic disease,motivational therapeutics, obesity, overweight, personcentred,psychosocial.